Experiential Learning in Action: How Design-Build-Test Projects Impact VTE Students’ Academic Motivation and Learning - Haji Ali, Ahmad Ikhwanuddin; Haji Bungsu, Hajah Jabaidah; Shahrill, Masitah (Journal of Technical Education and Training, 2025)
Students in Vocational and Technical Education (VTE) often struggle to connect theoretical knowledge with practical applications, leading to low academic motivation. Academic motivation is essential in shaping students’ future careers. Students’ passion and motivation while pursuing their studies may fade over time. Therefore, a strategy is needed to cultivate academic motivation and hone their passion for learning. Relating theory to practice in construction course is crucial to prepare students to meet industry needs. One of the strategies is implementing a Project-Based Learning (PBL) model such as Design-Build-Test (DBT) activities in this study involving a purposive sampling of Higher National Technical Education Certificate students from the Institute of Brunei Technical Education. This action research is aimed to evaluate the impact of implementing DBT projects on the students’ academic motivation. A mixed-method data collection technique was employed to examine students’ motivation levels and learning experiences before and after intervention: Academic Motivation Scale, field observations, semi-structured interviews, and lesson video recordings. Quantitative and qualitative data analyses of changes in academic motivation, common patterns of actions and behaviour via field observation checklists, and thematic analysis of students’ perceptions towards the implemented DBT project were carried out. Results from the analyses showed substantial improvements in students’ academic motivation through students’ collaboration in the DBT project, experiential learning, and opportunities it offered to students in relating theory and practice in construction field. The DBT projects strengthen connection between theoretical knowledge and practical applications, link gaps between conceptual understanding and competency skills in the students’ learning. The implication of this research findings showed the relevance of DBT projects in fostering experiential learning, and also provided evidence-based strategies for enhancing academic motivation, and useful contribution for improving curriculum design in construction programme, and career preparation to meet industry needs